An improved usage allocation method for deregulated transmission systems - Mustafa, M. W.; Shareef, H.; Ahmad, M. R. (IEEE, 2005)
This paper suggests an improved method for usage allocation to individual generators in a deregulated power system. Based on solved load flow, the method converts power injections and line flows into real and imaginary current injections and flows. These currents are then represented independently as real and imaginary current networks. Since current networks are acyclic lossless networks, proportional sharing principle and graph theory is used to trace the relationship between current sources and current sinks. The contributions from each current source are finally translated into power contributions to each load, line flows and losses. IEEE 14-bus test system is used to illustrate the effectiveness of the method. Comparison of the results with previous methods is also given.